2023
DOI: 10.4103/aian.aian_95_23
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Optimal Stimulation Frequency with Time for Gait Disturbances in Patients with PD after STN-DBS—A Longitudinal Study

Sruthi Kola,
Ravi Prakash Rangam,
Rukmini M Kandadai
et al.

Abstract: Aim: To assess the changes in frequency parameters of STN-DBS stimulation over 6 months required to optimize gait in PD patients. Methods: It’s a single center, open label longitudinal study of PD patients after STN-DBS with gait disorders. Gait assessment using stand–walk–sit (SWS) test and freezing of gait (FOG) scores were done at baseline and after 6 months. Gait was assessed in five frequencies settings, that is, 60 Hz, 90 Hz, 130 Hz, 180 Hz and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Although most of the studies have confirmed the benefits of low-frequency stimulation on FOG, it is unclear whether this benefit lasts longer. In the study by Huang C,[ 10 ] they assessed the changes in frequency parameters of STN-DBS stimulation over a period of 6 months that is required to optimize gait in PD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of the studies have confirmed the benefits of low-frequency stimulation on FOG, it is unclear whether this benefit lasts longer. In the study by Huang C,[ 10 ] they assessed the changes in frequency parameters of STN-DBS stimulation over a period of 6 months that is required to optimize gait in PD patients.…”
mentioning
confidence: 99%
“…In this study, as the voltage and pulse width were kept constant, the effect of DBS was most likely due to the frequency and could not be due to the spread of stimulation to adjacent areas. [ 10 ]…”
mentioning
confidence: 99%